The history of English : an introduction - Gramley, Stephan (London, United Kingdom : Routledge, 2019)
The History of English: An Introduction provides a chronological analysis of the linguistic, social, and cultural development of the English language from before its establishment in Britain around the year 450 to the present. Each chapter represents a new stage in the development of the language from Old English through Middle English to Modern Global English, all illustrated with a rich and diverse selection of primary texts showing changes in language resulting from contact, conquest and domination, and the expansion of English around the world. The History of English goes beyond the usual focus on English in the UK and the USA to include the wider global course of the language during and following the Early Modern English period. This perspective therefore also includes a historical review of English in its pidgin and creole varieties and as a native and/or second language in the Caribbean, Africa, Asia, and Australasia.
Part 1: Britain -- 1.The origins of English (before 450) -- Part 2: Early English in Britain -- 2.Old English: early Germanic Britain (450-700) -- 3.Old English: the Viking invasions and their consequences (700-1066/1100) -- 4.Middle English: the non-standard period (1066/1100-1350) -- 5.Middle English: the emergence of Standard English (1350-1500) -- 6.The early modern English period (1500-1700) -- Part 3: Britain and beyond -- 7.The spread of English (since the late sixteenth century) -- 8.Standard and non-standard English (Modern English) -- 9.English pidgins, English creoles, and English (since the early seventeenth century) -- 10. Grammatical change in Modern English -- 11.Pronunciation change in Modern English -- 12.Vocabulary and spelling change in Modern English -- Part 4: World-wide English -- 13.Global English (since 1945).
Includes bibliographical references and index.
Keywords: ENGLISH LANGUAGE